Forensic Medical Assessment of Thanatogenesis in the Experience of Gunshot Injuries - Julia V. Zbrueva (Indian Journal of Forensic Medicine & Toxicology, 2021)
Gunshot injury remains relevant at the present time and requires serious study. During the examination ofa gunshot injury, it is necessary to answer the investigator’s questions about the cause of death, the typeand rate of thanatogenesis, the distance of the shot, the sequence and mechanism of damage formation, andthe severity of the injury. The aim of the study was to determine the type of thanatogenesis in death fromvarious types of gunshot injuries. Standard methods of sectional research, forensic histological methods,morphological and statistical analysis, supplemented with semi-quantitative technologies of thanatogeneticanalysis were used in the study. The material for this study was 85 cases of death from gunshot injuries,which was distributed by gender, age, location of the injury, type and rate of thanatogenesis, type of gunshotinjury (bullet and shotgun wounds), the distance of the shot and the duration of hospital stay.